Trifluoroacetylazobenzene for optical and electrochemical detection of amines1. Issue 8 (28th February 2015) - Lin, Jhih-Fong; Kukkola, Jarmo; Sipola, Teemu; Raut, Dilip; Samikannu, Ajaikumar; Mikkola, Jyri-Pekka; Mohl, Melinda; Toth, Geza; Su, Wei-Fang; Laurila, Tomi; Kordas, Krisztian
<x xml:space="preserve">Abstract</x> Optical and electrochemical sensors based on 4-(dioctylamino)-4′-(trifluoroacetyl)azobenzene and its Nafion®–SWCNT composites show potential for practical applications in detecting various kinds of amines.